2012
DOI: 10.1038/nature11742
|View full text |Cite
|
Sign up to set email alerts
|

TET2 promotes histone O-GlcNAcylation during gene transcription

Abstract: SummaryTET enzymes including TET1, 2 and 3 convert 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC)1 and regulate gene transcription2-5. However, this molecular mechanism by which TET family enzymes regulate gene transcription remains elusive5-6. Here, using protein affinity purification, we searched for functional partners of TET proteins, and found that TET2 and TET3 associate with OGT, an enzyme that by itself catalyzes O-GlcNAcylation in vivo7-8. TET2 directly interacts with OGT, which is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
476
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(510 citation statements)
references
References 35 publications
19
476
0
5
Order By: Relevance
“…The functions of most histone O-GlcNAcylations are currently not clear, nor do we completely understand how OGT is recruited to chromatin, although some progress has been made. It is known that OGT can bind to corepressor mSin3A (21) and also associate with the DNA demethylase TET family proteins TET2 and TET3 and potentiate TET family protein-mediated gene activation (22)(23)(24)(25). Another critical mediator of OGT is the polycomb repressive complex 2 (PRC2).…”
mentioning
confidence: 99%
“…The functions of most histone O-GlcNAcylations are currently not clear, nor do we completely understand how OGT is recruited to chromatin, although some progress has been made. It is known that OGT can bind to corepressor mSin3A (21) and also associate with the DNA demethylase TET family proteins TET2 and TET3 and potentiate TET family protein-mediated gene activation (22)(23)(24)(25). Another critical mediator of OGT is the polycomb repressive complex 2 (PRC2).…”
mentioning
confidence: 99%
“…Yu and colleagues used streptavidin-binding peptide (SBP)-tagged TET proteins as bait and identified OGT as an interaction partner of TET2 and TET3, but not TET1 in mESCs. The interactions were further confirmed in 293T cells [10]. Using a flag-tagged biotinylated form of OGT, Pasini's group found that TET1 and TET2 were stable partners of OGT in mESCs [11].…”
mentioning
confidence: 76%
“…It has been shown that TET proteins associate with either various histone modifications including the methylation of H3K4 and H3K27 or epigenetic regulators such as PRC2 complex and SIN3A co-npg repressor complex [2], suggesting that TET proteins could employ multiple mechanisms to regulate chromatin contexts with respect to the control of gene expression. Notably, three groups recently demonstrated that TET proteins can physically interact with O-linked β-N-acetylglucosamine (O-GlcNAc) transferase (OGT) [10][11][12]. OGT is a unique glycosyltransferase that modifies hundreds of proteins by transferring single O-GlcNAc onto serine/threonine residues, thus participates in signal transduction and transcriptional regulation [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cette activité accrue permet à son tour de glycosyler la sous-unité HCF1 (host cell factor-1) du complexe SET1/ COMPASS, ce qui stabilise le complexe sur la chromatine et promeut la triméthyla-tion de l'histone H3 ainsi que l'activation transcriptionnelle [5]. Ce lien physique et fonctionnel a été confirmé par d'autres laboratoires qui ont également montré que TET1 était capable d'interagir avec OGT dans des cellules embryonnaires murines, et que TET2 participe à la glycosylation d'H2B dépendante d'OGT [7,8]. Plusieurs articles ont également décrit que les trois protéines TET peuvent être à leur tour glycosylées par OGT, ce qui (1) la glycosylation du complexe SET1/COMPASS sur sa sous-unité HCF1, et (2) la glycosylation de l'histone H2B.…”
Section: Potentiels Rôles Du Lien Tet-ogt Dans La Pathogenèseunclassified